STANDARD NEEDS INFORMATION SYSTEM (SPECIFICATIONS) MOBILE WEB BASED - Widiawati, Widiawati (JMBI (Journal of Marketing and Business Intelligence), 2023)
Toko Iwan is a business engaged in the sale of basic necessities in the Talangpadang market, Talangpadang sub-district, Tanggamus district, Lampung. Iwan's shop sells various kinds of basic household needs such as rice, sugar, noodles, cooking oil, flour and so on. In the process of recording transaction data at this store, it still uses a manual method using paper and pen media so that errors are often encountered and it is difficult to find out the stock of goods that are still available in the warehouse. The ordering process at this store is still via whatsapp, sms, telephone and coming directly to the store. The research method used is observation, interviews and literature study. This web-based sales system was developed using the waterfall development method, with the PHP programming language and the database used is MySQL. The design of this web-based information system is very useful in today's digital era and can make business activities at Toko Iwan more effective and efficient.